Device-related infections in long-term healthcare facilities: the challenge of prevention. (April 2014) - Mutters, Nico T; Günther, Frank; Heininger, Alexandra; Frank, Uwe
ABSTRACT: : The world is aging and the number of elderly multimorbid patients is steadily increasing. The limited numbers of acute care beds in hospitals, in addition to the need to reduce costs, has led to the introduction of efficient discharge policies, which in turn have increased demand for beds in nursing homes and long-term care facilities (LTCFs). As a consequence, the number of postacute LTCF residents is rising, as is the number of residents requiring complex medical care delivered by use of indwelling medical devices. These devices place patients at a heightened risk for infection. Furthermore, infection control resources in LTCFs are often limited. This article reviews the preventive measures that should be taken in LTCFs to reduce the risk of device-related infections.